Prevalence of depression and stress among the first year students in Suranaree University of Technology, Thailand - Areerat Siripongpan; Karunpong Phattaramarut; Niwatchai Namvichaisirikul; Settawit Poochaya; Paramate Horkaew (Health Psychology Research)
The objectives of this study were to evaluate the level of depression and stress among the first-year students at Suranaree University of Technology (SUT) and to compare the level of depression and stress among the samples, classified by demographic factors, including gender, domicile, and problem. This research has been approved by the SUT's Research Ethics Committee. The study period was between July and August 2018. The online, self-report questionnaire was used as a research instrument to collect data from the sample of SUT first-year students. The total number of first-year students at SUT was 3,552 and the response rate was 65.15%. The major findings revealed that 7.0% and 51.1% of them were suffering from depression, and pathological stress, respectively. In addition, the prevalence of depression and pathological stress was higher in female samples than in other gender groups. The findings would suggest that related activities should be organized to promote students' awareness of their suffering and self-control in order to prevent further depression and pathological stress.